1961
DOI: 10.1085/jgp.44.6.1121
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Studies of the Gain and Exchange of Calcium in Frog Skeletal Muscle

Abstract: (1) The Ca ++, Na +, and K + contents of frog sartorius muscles were found analytically after exposure to various media including some containing labeled Ca ++. (2) During storage in media with 100 to 120 mM Na + and 1 mM Ca ++ both Na + and Ca++ are gained while K + is lost; there is a high correlation between Na + and Ca++ gains. (3) When Ca ++ gain occurs from a solution containing labeled Ca++ there is also some exchange of the original Ca++ with the labeled Ca++. The amount exchanged is considerably less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

1963
1963
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 7 publications
3
14
1
Order By: Relevance
“…Taken together, these observations suggest that the mechanical potentiation caused by Na § deprivation is correlated with an increase in myoplasmic Ca 2+. In agreement with this interpretation, it has been reported that low [Na+]o increases the content of calcium in frog muscle (Cosmos & Harris, 1961). An increase in intracellular calcium would favour calcium release by SR through a calcium-induced-calcium release mechanism.…”
Section: Sodium Ions and Contractionsupporting
confidence: 74%
“…Taken together, these observations suggest that the mechanical potentiation caused by Na § deprivation is correlated with an increase in myoplasmic Ca 2+. In agreement with this interpretation, it has been reported that low [Na+]o increases the content of calcium in frog muscle (Cosmos & Harris, 1961). An increase in intracellular calcium would favour calcium release by SR through a calcium-induced-calcium release mechanism.…”
Section: Sodium Ions and Contractionsupporting
confidence: 74%
“…Although the efflux of Ca across the surface membrane therefore represents only a small fraction of the Ca changes occurring within the fibre during a response, it was of interest to examine the processes that determine the transport of this divalent ion and in particular whether Ca and Mg share the same transport system in this preparation (see Ashley & Ellory, 1972). There are at least two different Ca pumps which operate in cells; an ATP Ca MOVEMENTS IN SINGLE MUSCLE FIBRES requiring, Na-independent system is found in red cells (Schatzmann, 1966), the membranes of the sarcoplasmic reticulum (Ebashi & Lipmann, 1962;Hasselbach & Makinose, 1961 and in some other preparations, such as L cells (Lamb & Lindsay, 1971): while in excitable tissues, such as nerve (Baker, 1972), synaptosomes (Blaustein & Wiesmann, 1970), heart muscle (Reuter & Seitz, 1968) and skeletal muscle (Cosmos & Harris, 1961;Baker, 1972;Dipolo, 1973), the transport of Ca depends mainly upon the downhill movement of Na ions. It is difficult to investigate the ATP-dependence of the Ca transporting system in muscle since highenergy phosphate compounds are required to maintain the Ca stores within the sarcoplasmic reticulum and even in dialysed barnacle muscle fibres, there is still sufficient ATP present to activate completely the Na pump (Dipolo, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Lolley's result (57) showed that the calcium and sodium contents of the incubated tissue were dependent on the concentration of calcium in the outer fluid, but even when the sodium content of the tissue increased due to stimulation, the calcium content of the tissue did not follow this increase but showed no change, or rather had a tendency to decrease. The existence of calcium transport has been evidenced (57,58) and, in muscle and liver with medium low in sodium, it seems that calcium is taken up from the medium (58,59). Judah et al (58) concluded, by ob serving the extrusion of calcium from the liver slices being greatly reduced by the low external sodium, that calcium transport was dependent upon a normal sodium transport and calcium competed with sodium for the transport site.…”
Section: Besides Itmentioning
confidence: 99%